1
$\begingroup$

I need to factorize $ab -a -b +1$. I know that the answer is $(a -1)(b -1)$ can anyone give me some tips on how to do it?

$\endgroup$
1
$\begingroup$

$ab-a-b+1=a(b-1)-(b-1)=a(b-1)-1(b-1)=(a-1)(b-1)$

$\endgroup$
  • 1
    $\begingroup$ wow, thanks very much, I didn't saw "-b +1= -1(b-1)" $\endgroup$ – user429624 Mar 27 '17 at 0:32
1
$\begingroup$

You can apply the distributive law twice: \begin{align*} ab - a - b +1 = a(b-1) - (b-1) = (a-1)(b-1) \end{align*}

$\endgroup$
  • $\begingroup$ thanks I didn't saw "-b +1 = -1(b -1)" $\endgroup$ – user429624 Mar 27 '17 at 0:33

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.